Avoid yelling “stop thief!” and work disability prevention due to an occupational disease - Kuijer, P. Paul FM; Smits, Paul B.; van der Molen, Henk F.; van Dijk, Frank JH (Scandinavian Journal of Work, Environment & Health, 2013)
Kolstad and colleagues (1) reported on a well-conducted prospective cohort study among 2304 patients referred to an occupational medicine department of a university hospital in Denmark to assess whether the notification of an occupational disease increases the risk of work disability. Working employees with a notification had an increased risk of work disability with a hazard ratio of 1.4 [see table 2 (1]). Their recommendation is that “compensation systems should ensure that only workers with high odds of compensation are notified and physicians should consider the risk of exclusion from the job market before notifying a patient”. This is remarkably outspoken advice for such a delicate topic in occupational health. We believe this recommendation might be one step ahead of their findings and, more importantly, might be counterproductive for the prevention of work disability. First, regarding the evidence base, the notified group differs considerably from the non-notified group at baseline regarding prognostic factors for work disability: for instance there are more blue-collar workers (76% versus 54%), ergonomic exposures (51% versus 26%) and work-related disabling diseases such as dorsalgia (14% versus 7%), shoulder lesions (10% versus 4%), irritant contact dermatitis (8% versus 2%), Raynaud’s syndrome (5% versus 1%), and carpal tunnel syndrome (5% versus 1%). In addition, no adjustments were made for physical and mental job demands. The authors are aware of this given their statement in the conclusion “… data analyses may not have fully accounted for the poorer vocational prognosis…”. Moreover, work disability was in fact defined as sick leave of >12 weeks in the upcoming year, independent of the notified occupational disease. From a national survey in the Netherlands, we know that among working patients, who presume that their disease is mainly or partly work-related and who were not notified, the duration of sick leave is more than twice as long when taking into account the type of disease: 16 versus 7 days (2). A similar effect was found among Dutch patients without employment who were not notified about their occupational disease: the sickness absence lasted 1.5 times longer when the sick-listing was due to an occupational disease, and 2.6 times more often the sick-listed worker reached – after two years of sick leave – the work disability assessment required for the entitlement of disability benefits. At that time, they were granted the disability benefits twice as often. Secondly, we consider an intervention study to be more appropriate to support this kind of recommendation, preferably a (randomized) controlled study. No description is given about the potential impact of the notification: how was the patient notified about the occupational disease? At what point in time was this done since the complaints arose? How were the consequences for return-to-work discussed and what care was provided to support sustainable return-to-work among this vulnerable population? Especially in the case of an occupational disease, timely and tailored integrated care might be necessary to accomplish sustainable return-to work, with an important role for both employer and employee and of course the occupational physician (4, 5). Finally, by the nature of their job, occupational physicians should discuss as soon as possible the work-related aspects of a disease with their patient, regardless of the compensation mechanisms at stake. Many patients themselves have – true or false – perceptions and expectations about the work-relatedness of their complaints. In the Netherlands, more than 50% of the employees on sick leave due to mental health complaints and musculoskeletal complaints of the low back and upper extremity are of the opinion that work is mainly or partly the cause (2). Therefore, instead of a recommendation that might discourage occupational physicians from discussing the work-relatedness of the disease with their patients, a timely diagnosis and appropriate care and intervention at the workplace seems warranted to prevent work disability in the case of an occupational disease (6). We do not expect a security officer to remain silent while witnessing a theft; the same goes for an occupational physician unwilling to address the topic and consequences of an occupational disease.
Keywords: commentary; notification of occupational disease; occupational disease; work disability